Individualism–collectivism as a moderator of the work demands–strains relationship: A cross-level and cross-national examination - Yang, Liu-Qin; Spector, Paul E; Sanchez, Juan I; Allen, Tammy D; Poelmans, Steven; Cooper, Cary L; Lapierre, Laurent M; O'Driscoll, Michael P; Abarca, Nureya; Alexandrova, Matilda; Antoniou, Alexandros-Stamatios; Beham, Barbara; et al. (Journal of International Business Studies, 2012)
Surveying 6509 managers from 24 countries/geopolitical entities, we tested the process through which individualism–collectivism at the country level relates to employees’ appraisals of and reactions to three types of work demands (i.e., work hours, workload, and organizational constraints). Our multilevel modeling results suggested that, while working the same number of hours, employees from individualistic countries reported a higher perceived workload than their counterparts in collectivistic countries. Furthermore, relationships of perceived workload and organizational constraints with job dissatisfaction and turnover intentions were stronger in individualistic than in collectivistic countries. Importantly, results of supplementary analyses suggested that the cultural value of individualism–collectivism moderated the mediation effect of perceived workload between work hours and both job dissatisfaction and turnover intentions. Our findings highlight the need to expand contemporary theories of work stress by applying multilevel approaches and incorporating cross-national differences in dimensions such as individualism–collectivism while studying how employees appraise and react to important work stressors.